Transitivity and critical discourse analysis on a testament: A woman’s involvement in jihad - Fahmi Gunawan; St Kuraedah; Abdul Muiz Amir; M Faruq Ubaidillah; Saad Boulahnane (Studies in English Language and Education, 2023)
While a plethora of scholars have explored a growing body of research on women’s involvement in Jihad, there is still a paucity of studies addressing it using the hybridity of transitivity analysis and critical discourse analysis. The present study examined a testament left by an Indonesian woman involved in what she fallaciously called ‘Jihad’. To collect the data, the document analysis was adopted, meanwhile, Halliday and Matthiessen’s transitivity analysis (2004) and Fairclough’s critical discourse analysis (2003) were employed to analyze the data. The findings demonstrated that the experience of the woman’s involvement in jihad was described by the dominant use of material process verbs (59.4%), followed by relational process (19%), mental process (13.5%), and verbal process (8.1%). The transitivity analysis showcases that the testament is not an average text with a religious message or instructions to deal with the left property; instead, it contains a message of the Salafi Jihadist ideology of the Islamic State of Iraq and Syria (ISIS), which might put people’s lives in peril. The five core teachings of ISIS encapsulate the message of ideological teachings, including jihad (struggle in the context of religious war), takfiri (ex-communication), al-wala’ and al-barra’ (loyalty and disavowal for the sake of God), tauhid (unitary oneness of God), and tahkimiyah (the rule of God – both religiously and politically). The study findings implicate that we must raise awareness of all kinds of testaments left by the jihadi woman because these testaments may contain a global jihadist doctrine. With this in mind, we will not be easily persuaded to join a Salafi jihadist organization.